Guy Halsall, ed., Humour, History and Politics in Late Antiquity and the Early Middle Ages, Cambridge, 2002, 208 pp. ISBN 0 521 81116 3 (Minerva, 2019)
Review: Guy Halsall, ed., Humour, History and Politics in Late Antiquity and the Early Middle Ages, Cambridge, 2002, 208 pp. ISBN 0 521 81116 3